A Novel Design of Conjugated Polymer/TiO2 towards Photocatalytic Activity under Visible Light. Issue 1 (May 2020) - Liu, Linlin; Duan, Qian
Abstract: In this work, we successfully designed and functioned a novel thiophene-based conjugated polymer to match with TiO2, forming a range of PDPPT-T-COOH/TiO2 heterostructure. The as-prepared PDPPT-T-COOH/TiO2 heterostructure showed the remarkable photocatalytic degradation performance of TC. Under visible light, the highest k value of PDPPT-T-COOH/TiO2 -3% heterostructure was 0.00652 min −1, which was 5.48 and 11.6 times that of a single PDPPT-T-COOH and TiO2 . The enhanced photocatalytic ability could be owed to the interfacial interaction and excellent migration efficiency of charge carriers between the heterojunction photocatalyst. This work may offer innovative feasibility to synthesize PDPPT-T-COOH/TiO2 heterostructure with high stability and superior photocatalytic activity.